Ways and means : Lincoln and his cabinet and the financing of the Civil War - Lowenstein, Roger (Penguin Press, 2022)
"In Ways and Means, journalist Roger Lowenstein reveals the unlikely story of how Abraham Lincoln used the urgency of financing the Civil War to transform a union of states into one united nation. Through a financial lens, he explores how this second American revolution, led by Lincoln, his cabinet, and his congress, changed the direction of the country"--